Antibody of goat zona pellucida-3 (gzp3) protein of mice(Mus musculus) block in vitro fertilization of mice as an animal model= Antibodi protein zona pelusida-3 kambing (gZP3) asal mencit(Mus musculus) mencegah ... - Imam Mustofa; Laba Mahaputra; Yoes Priyatna Dachlan; Fedik Abdul Rantam; Suwarno .; Widjiati .; Aucky Hinting (Jurnal Sain Veteriner, 2006)
The researchs of immunocontraception have done in ZP3 of several species, but have not been done in ZP3 of goat. In preliminary study, gZP3 protein was effective prohibited of graviditation of mice. The aim of this study was to prove the potency of gZP3 protein to prohibit in vitro fertilization of mice as an animal model. Antibody of gZP3 produced on mice. Immunized mice serum was analyzed using Elisa and Dot blotting method. Antibody of gZP3 supplemented into M-16 media for oocyte incubation, continued with in vitro fertilization. The result showed that antibody titer of immunized mice serum was higher (p